EKSPLORASI ETNOMATEMATIKA PADA PERMAINAN GOBAK SODOR - Umar Hamdan; Nur Wiji Sholikin (SOCIAL EDU: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study is to investigate ethnomathematics in the traditional Banyuanyar Probolinggon game Gobak Sodor on mathematical ideas like gradients, vectors, and point-to-point distance. Based on the information gathered and the data collected through observations and interviews, this study employs an anthropological approach to describe a thorough investigation of a culture. In order to comprehend ethnomathematics in relation to mathematical notions like vectors, gradients, and point-to-point distances, this study focuses on the Gobak Sodor game, one of the traditional games played in Banyuanyar Probolinggo. This demonstrates how mathematical ideas and methods of deepening in earlier research that have connections to geometric mathematical notions like flat shapes are related to the traditional game Gobak Sodor in Banyuanyar Probolinggo. The use of traditional game media in mathematics education can have advantages, such as helping students visualize mathematical topics in a realistic setting, which improves their comprehension.